Analisis Perbandingan Implentasi Cara Distribusi Obat Yang Baik (CDOB) Pada Pedagang Besar Farmasi (PBF) BUMN Dan Non BUMN Di Wilayah Provinsi Riau - Suci Amaliya Indah Lestari Suci Amaliya Indah Lestari; Husnawati Husnawati; Seftika Sari (LPPM Universitas Abdurrab, 2025)
Drug distribution is a crucial step in ensuring the quality, safety, and availability of drugs in the community. Good Drug Distribution Practices (CDOB) are established as a standard by the Food and Drug Monitoring Agency (BPOM) for all Pharmaceutical Wholesalers (PBF). This study aims to compare the implementation of CDOB in state-owned and non-state-owned PBFs in Riau Province. The study used a mixed methods study approach. The research design used Sequential Explanatory by combining quantitative and qualitative methods. The quantitative approach used a cross-sectional design with instruments in the form of a CDOB checklist consisting of 12 CDOB aspects and in-depth interviews with Responsible Pharmacists (APJ). Quantitative data analysis was carried out by calculating the percentage (%) of conformity based on the results of the BPOM CDOB checklist form and the Chi-Square test. Qualitative data analysis was conducted descriptively through interviews using content analysis methods to identify discrepancies in the results of the BPOM CDOB checklist and to identify factors influencing CDOB implementation in state-owned and non-state-owned enterprises (BUMN) PBFs. The results showed that the overall compliance level of CDOB implementation reached 99.6% of the maximum score, with an average score of 114.5 out of a total score of 115. BUMN and non-BUMN PBFs achieved the same average score of 114.5/115 (99.6%). Almost all aspects of CDOB were implemented well, but BUMN PBFs still faced deficiencies in organizational and personnel aspects related to personnel discipline. Meanwhile, non-BUMN PBFs faced major challenges in buildings and equipment, particularly limited storage space and temperature control in cool rooms. A chi-square test showed no significant difference between BUMN and non-BUMN PBFs (p > 0.05). Factors influencing CDOB implementation include: competence and human resources, quality management systems, adequate facilities and infrastructure, and compliance with SOPs and regulations. In conclusion, the implementation of CDOB in state-owned and non-state-owned enterprise (BUMN) PBFs in Riau Province has been very successful, with a compliance rate of >99%. Although strengthening of human resources and storage infrastructure is still needed to ensure the quality of sustainable drug distribution.